Wild food plants with the potential to improve food and nutrition security may be threatened by timber extraction: A systematic review of the Brazilian context - Caetano, Roberta; Monique da Costa Santos, Élida; Zago Poian, Richard; Rosa Carvalho, Adriana; Ricardo Vasconcelos da Silva, Rafael; Muniz de Medeiros, Patrícia (Ethnobiology and Conservation, 2023)
Wild food plants can contribute to improving the food and nutrition security of local populations by promoting diet diversification and increasing the intake of micro- and macronutrients. However, many of these plants are also used as timber. Wild food species need to be identified and their food–wood use interactions need to be well understood for the development of conservation strategies, as species with the potential to improve food and nutrition security may be threatened by destructive extraction. This systematic review recorded and compiled nutritional information on woody plant species native to Brazil that are used by local populations for food and timber purposes, seeking to identify which species have a high overlap between food and timber uses as well as a high nutritional potential. A total of 635 woody species with timber and/or food uses were identified. Of this total, at least 42 species find application in all timber use categories analyzed in this study, being considered versatile. Comparison of ethnobiological and nutritional data revealed nine versatile species for which nutritional composition information was available, among which three stood out in terms of macronutrient contents, namely Anacardium occidentale L., Bauhinia cheilantha (Bong.) Steud., and Eugenia pyriformis Cambess. Many versatile species classified as threatened or in decline have not been the focus of nutritional studies, which signals the need for greater nutritional research efforts. It is also necessary to investigate whether food importance exerts any protective effect on these species, reducing timber use pressure (protection hypothesis).